Chemopreventive Properties Of Sulfated Polysaccharide Extracts From Sargassum Siliquosum J. G. Agardh (Sargassaceae) - ROSS D. VASQUEZ; JOHN DONNIE A. RAMOS; SAMUEL D. BERNAL (International Journal of Pharma and Bio Sciences, 2012)
Sulfated polysaccharides from brown seaweeds attracted extensive interest due to their numerous biological activities and structural diversity. Sulfated polysaccharides isolated from Sargassum siliquosum J. G Agardh were investigated for its chemopreventive potential using in vitro assays. Estimation of chemopreventive activity included antioxidant (cancer anti-initiation); Nitrite Assay (cancer anti-promotion) and cytotoxicity (cancer anti-progression) assays representing the 3 stage paradigm of carcinogenesis. Extracted water soluble polysaccharides containing sulfate were identified by FT-IR and Ashing Acid Digestion Ion chromatography with IR spectra comparable to standard fucoidan and alginate. Sulfated polysaccharides showed significant radical scavenging activity in DPPH radicals, significantly suppressed production of nitric oxide in LPS-stimulated promyelocytic leukemic cells (PML) and displayed significant antiproliferative activity in both Hep G2 and renal carcinoma cells in vitro. Results herein indicated that sulfated polysaccharide of S. siliquosum possesses chemopreventive activities and their use as potential natural reagents might for cancer therapy should be given priority.